IDENTIFIKASI TANAMAN KACANG-KACANGAN BERDASAR ZAT HARA LAHAN MENGGUNAKAN METODE ELECTRE (STUDI KASUS:DI KABUPATEN GUNUNGKIDUL) - Indrianingsih, Yuliani (Sekolah Tinggi Teknologi Adisutjipto, 2016)
This study aims to improve the economic value of farmers' land, so the land can be planted with legumes right by the soil nutrient. Many farming communities are still using the self-taught learning and experience from generation to generation in the determination of the types of legumes were planted them, causing yields are not optimal. And so we need a system that can help farmers to determine the type of legumes matching based nutrient soil to be processed. The study was conducted in the five District in Gunungkidul for data collection in the field. The results of data collection in the field can be a benchmark for decision makers farmers to determine the type of legume crops to be planted based on the criteria of soil nutrients . Criteria are a barometer of determining the type of legumes is the KTK, base saturation, O, Ca, C / N, Magnesium, Carbon. Determining the level of importance of each criterion and to calculate the value of suitability types of legumes based on each of these criteria were analyzed using ELECTRE. With this system the maximum expected agricultural output, thus increasing the economic value of Gunungkidul regency. Keywords : Identification, legumes, Electre